Synthesis, characterization, photophysics, and photochemistry of peripherally substituted tetrakis(quinolinylethylenephenoxy)-substituted zinc(ii) phthalocyanines - Ozdemir, Mucahit; Artuc, Gamze Ozgul; Akkurt, Barbaros; Yalcin, Bahattin; Satan, Umit; Durmuş, Mahmut; Bulut, Mustafa (Royal Soc Chemistry, 2021)
In this work, 2-chloro-6-methoxyquinoline-3-carbaldehyde was reacted with [4-(3,4-dicyanophenoxy)phenyl]acetic acid to obtain 2-(3,4-dicyanophenoxy)phenyl-4-(2-chloro-6-methoxyquinolin-3-yl)-3-butenoic acid as a phthalocyanine precursor. This compound was heated in 2-dimethylaminoethanol in the presence of zinc acetate to yield 2,9(10),16(17),23(24)-tetrakis[2-phenoxy-4-(2-chloro-6-methoxyquinolin-3-yl)-3-butenoic acid] substituted zinc(ii) phthalocyanine. Some thiols, namely n-butanethiol (R-1), n-hexanethiol (R-2), 3-sulfanylpropionic acid (R-3), and 7-sulfanyl-2H-1-benzopyran-2-one (R-4), were reacted with this zinc(ii) phthalocyanine compound. Nucleophilic aromatic substitution reaction occurred at the chloro substituent of the respective quinoline on the phthalocyanine framework. The fluorescence behavior, singlet oxygen generation, and photostability properties of these novel phthalocyanines were investigated. These compounds may be potential photosensitizers for photodynamic therapy and deserve further study.
Keywords: Langmuir-Blodgett-Films; Photodynamic Therapy; Metal-Free; Aluminum Phthalocyanine; Photovoltaic Properties; In-Vitro; Coumarin; Photosensitizers; Moieties